Conservation and Management of Endangered River Terrapin Batagur baska (Gray-1831) in West Bengal - Seth, Sukumar (Indian Forester, 1993)
Batagur baska the tropical marine turtle a threatened species at the estuary of the Ganges largely due to eco-ego complexities, has at the Sunderban Tiger Reserve shown certain phases of its life during hatching. Preliminary studies about their laying habitat, physical dimensions of eggs, the condition of the hatchlings etc are reported for the first time in details.